Posttraumatic rhinolith. - Meyer, J R; Quint, D J (American Journal of Neuroradiology, 1993)
Rhinolith, calcified concretion of a nidus within the nasal cavity, is a possible diagnosis for certain patients with densely mineralized lesions that appear benign and without bone destruction.